Survivin expression in ovarian cancer - Liguang, Z.; Peishu, L.; Hongluan, M.; Hong, J.; Rong, W.; Wachtel, M.S.; Frezza, E.E. (Experimental Oncology, 2007)
Aim: To examine the expression of survivin in benign ovarian tumors, ovarian carcinomas of different stages. Methods: We screened the expression of survivin mRNA by reverse transcription polymerase chain reaction in 114 ovarian tissue samples. Quantitative real-time PCR was used to estimate survivin mRNA levels in the samples with positive survivin expression. Results: No survivin mRNA was expressed in all normal ovarian specimens, while it appeared in 73% of ovarian carcinomas, 47% of borderline ovarian carcinomas and 19% of benign ovarian tumors. The survivin mRNA expression rate was positively associated with clinical stage (P = 0.026) and differentiation grade (P = 0.049). There was notably statistically significant difference in the survivin mRNA expression rate dependent on different histological types (serous, mucinous, endometrioid, P = 0.008), but not – dependent on lymph node metastasis (P = 0.921) and ascites (P = 0.87). In tissues with positive expression of survivin, we also found that mean survivin mRNA expression levels were higher in ovarian carcinomas than that in benign ovarian tumors and borderline ovarian carcinoma tissues (P < 0.001). Among ovarian carcinomas, the high survivin mRNA expression levels correlated with the clinical stages, differentiation grade, lymph node metastasis, but not — with ascites and histological type. Conclusion: Our study suggest that survivin is associated with progression of ovarian carcinoma. Цель: исследовать экспрессию сурвивина в доброкачественных и злокачественных новообразованиях яичника. Методы: экспрессия
мРНК сурвивина исследована методом RT-PCR в 114 образах ткани яичника человека. Для установления уровня экспресии
мРНК сурвивина применяли количественный PCR в режиме реального времени. Результаты: экспрессия мРНК сурвивина
не выявлена в образцах нормальной ткани яичника, но зарегистрирована в 73% случаев рака яичника, 47% случаев серозных
опухолей яичника серозного типа и 19% образцов доброкачественных опухолей. Установлена положительная зависимость между
уровнем экспрессии мРНК сурвивина и клинической стадией заболевания (P = 0,026), и степенью дифференцировки опухоли
(P = 0,049). Выявлена статистически значимая зависимость уровня экспрессии мРНК сурвивина от гистологического типа
опухоли (серозного, мукозного, эндометриоидного, P = 0,008) и отсутствие таковой от наличия метастазов в лимфатических
узлах (P = 0.921) или асцита (P = 0.87). Также установлено, что средние уровни экспрессии мРНК сурвивина выше при раке
яичника, чем в ткани доброкачественных новобразований или серозных опухолей яичника пограничного типа (P < 0,001).
При раке яичника высокий уровень экспрессии мРНК сурвивина коррелировал с клинической стадией заболевания, степенью
дифференцировки опухолевых клеток, но не коррелировал с гистологическим типом новообразования. Выводы: результаты
свидетельствуют о том, что экспрессия сурвивина ассоциирована с прогрессией рака яичника.
Ключевые слова: сурвивин, рак яичника, опухолевая прогрессия.